Single- vs. multiple-set strength training in women - Schlumberger, A.; Stec, J.; Schmidtbleicher, D. (The Journal of Strength and Conditioning Research, 2001)
The aim of this study was to compare the effects of single-set and multiple-set strength training in women. Twenty-seven women (aged 20-40 years) with basic experience in strength training were randomly allocated to either a single-set group (n = 9), a 3-set group (n = 9), or a nontraining control group (n = 9). Both training groups underwent a whole-body strengthening program, exercising 2 days a week for 6 weeks. Exercises included bilateral leg extension, bilateral leg curl, abdominal crunch, seated hip adduction/abduction, seated bench press, and lateral pull-down. The single-set group's program consisted of only 1 set of 6-9 repetitions until failure, whereas the multiple-set group trained with 3 sets of 6-9 repetitions until failure (rest interval between sets, 2 minutes). Two times before and 3 days after termination of the training program, subjects were tested for their 1 repetition maximum strength on the bilateral leg extension and the seated bench press machine. Data were analyzed using a repeated-measures analysis of variance, Scheffé tests, t-tests, and calculation of effect sizes. Both training groups made significant strength improvements in leg extension (multiple-set group, 15%; single-set group, 6%; p 0.05). However, in the seated bench press only the 3-set group showed a significant increase in maximal strength (10%). Calculation of effect sizes and percentage gains revealed higher strength gains in the multiple-set group. No significant differences were found in the control group. These findings suggest superior strength gains occurred following 3-set strength training compared with single-set strength training in women with basic experience in resistance training.